2014
DOI: 10.1039/c3ra46854b
|View full text |Cite
|
Sign up to set email alerts
|

Emission and surface properties of main-chain type polybenzoxazine with pyridinyl moieties

Abstract: A main-chain type polybenzoxazine, PBz (1), with pyridinyl moieties was prepared. When the THF dilute solution of PBz (1) was protonated with HCl, a new absorption signal at 458 nm was observed in the UV-vis spectrum. After being excited at 458 nm, a strong emission at 570 nm was observed in the fluorescence spectrum. This result suggests that the pyridinyl-containing PBz (1) can be used as a proton sensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…We attribute the signal at 250 nm (peak 1) to the high-energy p-p* transition, and those at 277 and 304 nm (peaks 2 and 3, respectively) to the LE p-p* transition and the intramolecular charge-transfer (ICT) p-p* transition, respectively, from the relatively strongly electron donating TPA moieties to the relatively weakly electron donating BZ moieties, as a hybridized local and charge-transfer (HLCT) transition. 58,59 Upon increasing the number of TPA groups in the hyperbranched TPA-BZs, a small bathochromic shi occurred in the absorption spectrum (peak 2) in Fig. 7A, possibly the result of the increased conjugation length.…”
Section: Uv-vis Absorption and Pl Emission Spectra Of Hyperbranched Tmentioning
confidence: 99%
“…We attribute the signal at 250 nm (peak 1) to the high-energy p-p* transition, and those at 277 and 304 nm (peaks 2 and 3, respectively) to the LE p-p* transition and the intramolecular charge-transfer (ICT) p-p* transition, respectively, from the relatively strongly electron donating TPA moieties to the relatively weakly electron donating BZ moieties, as a hybridized local and charge-transfer (HLCT) transition. 58,59 Upon increasing the number of TPA groups in the hyperbranched TPA-BZs, a small bathochromic shi occurred in the absorption spectrum (peak 2) in Fig. 7A, possibly the result of the increased conjugation length.…”
Section: Uv-vis Absorption and Pl Emission Spectra Of Hyperbranched Tmentioning
confidence: 99%
“…All curing results are summarized in Tables S1-S3 and Figure 4 by using Gaussian function by controlling the wavenumber and half-width within ± 10 cm −1 . In our previous report, we revealed that the free energies of polymer surfaces can be altered by changing the degree of intra-or intermolecular hydrogen bonding [10][11][12][13][14][15][16]. A decrease in intermolecular hydrogen bonding leads to a decrease in the surface free energy of a polymer; conversely, the surface free energy of a polymer increases with increasing intermolecular hydrogen bonding.…”
Section: Temp ( • C)mentioning
confidence: 97%
“…We have shown that a portion of the intramolecular hydrogen bonds in the polybenzoxazine system converts into intermolecular hydrogen bonds upon exposure to UV radiation, resulting in a higher surface free energy and, consequently, a higher hydrophilicity [11,12]. Lin et al found that as-cured main-chain-type polybenzoxazine precursors also exhibit strong intramolecular hydrogen bonding and low surface free energies [13,14]. Apart from the polybenzoxazine system, we have also revealed that poly(vinylphenol; PVPh) exhibits a tremendously low surface energy through thermal treatment due to a loss in the fraction of intermolecular hydrogen bonds involving its -OH groups [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Polybenzoxazine is a new, developing phenolic-type thermoset resin that has attracted much attention in recent years because of its outstanding properties, and the different forms of polybenzoxazine (such as bulk [1][2][3][4][5], film [6][7][8][9][10][11][12][13][14][15][16][17][18][19], aerogel [20][21][22][23][24][25], and porous membranes [26,27]) and their various applications have been studied extensively. At the same time, production of nanofibers from polybenzoxazine resins and incorporation of the polybenzoxazines into the other polymeric nanofibers for the functionalization and enhancement of the existing properties is a developing area.…”
Section: Introductionmentioning
confidence: 99%